Utilization of Multimedia Technology for Instructional Media - Chandra Anugrah Putra (Pejabat Karang Mengarang UPSI, 2018)
The study of this theory aims to find out how animation as multimedia-based learning media can help the learning process undertaken by teachers and learners, and help students understand the visualization provided by the teacher. The rapid development of technology makes technology become one of the necessities that must be possessed by humans to help solve a problem encountered. One of the technological developments that are currently emerging technology-shaped gadgets. Lifestyle development of people who prefer practicality began to bring gadgets. There are new challenges for teachers from the rapid development of the world of informatics technology and electronic devices such as gadgets, that is how teachers can utilize gadgets to optimize learning in the classroom. Because like or dislike, our students are big in the digital age, so the teachers as much as possible adjust to the development of technology.